Policy Making in Optimizing Inventory Control with Continous and Periodic Review Method at PT. XYZ - Reka Nur Aini Reka; Enny Aryanny (Universitas Muhammadiyah Sidoarjo, 2022)
PT. XYZ is a company enganged in the garment sector that produces office uniforms, polo t-shirts and t-shirts with the highest demand for polo t-shirt products from lacos 20S Black cloth. Based on company data and the results of interviews with informants, it found that companies often eperience stockout and overstock of supplies of lacos 20S black cloth due to fluctuating demand. This study to control inventory by comparing the company method with the method of Continuous Review (s,S) System, (S,Q) System and Periodic Review (R,s,S) System, (R,S) System to obtain minimum total cost of inventory. Based on the calculation using the company method, the total cost of inventory is Rp 643.487.400 and the minimum total cost of inventory using the Continuous Review (s,Q) System method is Rp 635.880.585 with savings of Rp 7.606.815 and the percentage of cost reduction is 1,18%. The forecasting needs for April 2021 to March 2022 using the Continuous Review (s,Q) System method, the order quantity is 378 Kg and the reorder point is 133 Kg with a total inventory cost is Rp 767.415.089.